Socialization And Counseling on How yo Use Appropriate Technology for Wood Crushing Machines in Sukaluyu Village, Pangalengan District, Bandung Regency - Yuningsih, Siti Hadiaty; Ali, Ilham; Setiawan, Haris (Research Collaboration Community (Rescollacom), 2026)
The purpose of this community service program is to (1) Provide knowledge to village communities about how to utilize appropriate technology in everyday life. (2) Provide guidance in completing the utilization of appropriate technology according to the needs desired by the village community properly and correctly. The method of implementing this community service activity is carried out by providing guidance on how to apply and complete the tools that will be used at the village, sub-district, district, provincial, and national levels. (1) At the beginning of the activity, provide basic knowledge and concepts about the material on how to make the tools that will be used. (2) Provide training and examples in completing an activity about appropriate technology that will be used. (3) The final stage, the community is asked to be able to apply it in everyday life properly and correctly, so that from this community service activity the community can utilize existing resources for the common good, namely in oyster mushroom cultivation.